MENINGKATKAN KINERJA GURU DALAM PENERAPAN PENDEKATAN REALISTIK MELALUI TEKNIK SUPERVISI KUNJUNGAN - Rosmaida Rosmaida (EJoES (Educational Journal of Elementary School), 2020)
The purpose of this study was to find out through classroom visit supervision techniques can improve teacher performance in the application of a realistic approach in SD Negeri 094130 Dolokmaraja. This school action research was carried out in 2 cycles with the application of a realistic approach. The research subjects were 6 teachers of SD Negeri 094130 Dolokmaraja. The data collection method was used, the observation observation sheet, and the photos. Based on the results of the study, it was found that in the first cycle the class average value was 76.1%. In the second cycle of action with the application of a realistic approach through the classroom visit supervision technique, it was found that the class average value increased, namely 91.9 and the value of teacher activity observation increased to reach 100%. Thus it can be concluded that through classroom visit supervision techniques the application of a realistic approach increases.